Conversor CC-CA monofásico de dois estágios sem capacitor eletrolítico e filtro de saída LCL - Dias Júnior, Antônio José Sousa (2018)
This work aims to design a bidirectional DC-AC converter for applications in DC microgrid connected to the local power grid. The proposed inverter is composed of two stages: DC-DC input stage and DC-AC output stage. An active filter is also used to compensate the AC component of 120 Hz on the DC link, reducing the capacitance required and increasing the useful life of the converter, thus eliminating the use of electrolytic capacitors. On the output of the DC-AC stage is used a LCL filter with passive damping, by inserting a resistor in series with the filter capacitance, which results in a low harmonic content for the current injected in the grid. The validation of the proposed control is performed through simulations in software. An experimental prototype was also developed with the purpose of validating the simulation results.